The progress in sustainable energy in Colombia (2014)
Sustainable energy is important for the development and welfare of the population, and analysis of how the countries use their energy is a key to strengthening productive activities from an environmental protection perspective. This study seeks to determine the progress in sustainable energy in Colombia over the last decade by analysing three features, such as access to energy, energy efficiency and renewable energy. For every feature, this study defines several indicators determining their trends with the primary results, achievements, gaps and barriers within the institutional and policy framework. The results of this analysis demonstrated that Colombia has achieved significant advances in its access to energy, has recognized the need to increase energy efficiency and has directed actions for the application of renewable energy in specific projects exploiting the significant potential of this energy. The Colombian government has formulated two regulations (Law 691/2001 and Decree 3683/2003) and the PROURE program with Resolution 180919/2010 to implement various measures to promote sustainable energy. However, this country faces several challenges to achieve improved energy use that decreases the environmental impacts while strengthening economic growth and development. © 2014 Nova Science Publishers, Inc.